2013
DOI: 10.1177/0095327x12466071
|View full text |Cite
|
Sign up to set email alerts
|

The Theocratization of the Israeli Military

Abstract: This article portrays the theocratization of the Israeli military. At the center of this process stands the national-religious sector, which has significantly upgraded its presence in the ranks since the late 1970s. It is argued that four integrated and cumulative processes gradually generated this shift toward the theocratization of the Israeli military: (1) the crafting of institutional arrangements that enable the service of religious soldiers, thereby (2) creating a critical mass of religious soldiers in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 11 publications
0
33
0
Order By: Relevance
“…However, this is true for only one fifth of the respondents, especially among conscription soldiers. In addition, it seems that the study of religion in the military may provoke the question of the role of institutionalized religion agents in the military as opposed to the military and political control (Eberle & Rubel, 2012;Levy, 2014;Røislien, 2013). Yet the current study sheds light on the individual soldier's coping style and its relation to combat motivations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this is true for only one fifth of the respondents, especially among conscription soldiers. In addition, it seems that the study of religion in the military may provoke the question of the role of institutionalized religion agents in the military as opposed to the military and political control (Eberle & Rubel, 2012;Levy, 2014;Røislien, 2013). Yet the current study sheds light on the individual soldier's coping style and its relation to combat motivations.…”
Section: Discussionmentioning
confidence: 99%
“…However, religious faith was not significantly examined in the context of the motivation to fight in actual military undertakings. Most of the current research is centered on the political control of the military (Levy, 2014) or the enlistment into the IDF in the wider Israeli context (Røislien, 2013) and the ensuing internal structure of the military (Libel & Gal, 2015). The connection between motivation to fight, stress, and coping with it in times of combat was also not extensively explored.…”
Section: Combat Motivationmentioning
confidence: 99%
“…4 This case study is the most prominent in a list of identity struggles that include the dispute on joint military service for men and women (Levy 2010); struggles over the past decade within the IDF between the Education corps and the Military Rabbinate (Cohen et al 2016); and the religionization discourse which began in 2010 on the empowerment of religious factors and their influence on the IDF. Yagil Levi's studies are the most identified with the 'religionization' term (see, for instance, Levy 2016Levy , 2014, while Statman (2019) suggests that the religionization thesis should be rejected (For a discussion on the presence or absence of religionization in the IDF, see for instance Gal and Libel 2012). Other confrontations, such as stricter terms for growing beards-among the prominent external features of certain religions such as Judaism and Islam (Rosman-Stollman 2005, pp.…”
Section: Women's Singing: Between Religious Prohibition and Central Cmentioning
confidence: 99%
“…Since the advent of the pre-military academy revolution, neo-liberal opinion leaders in academic, media and political spheres within Israeli discourse have advanced moral panic (Goode & Ben-Yehuda, 1994) over what they call religionization or theocratization (Levy, 2014) of the army: a fear that the growing numbers of Religious-Zionist commanders will lead to a situation where rabbis, rather than senior commanders, will hold real authority, and there will be an attempt to imbue the IDF with a religious culture and militarist-colonialist aims. The real fear is that 'the loyalty [to democracy] discourse amongst Religious-Zionism is a bluff' (Shani, 2015).…”
Section: Moral Panic In the Face Of Religionization (Hadata) And Theomentioning
confidence: 99%